Meningkatkan pemahaman konsep perubahan bentuk benda melalui penerapan model pembelajaran treffinger pada siswa kelas IV sekolah dasar - Peduk Rintayati; Jenny Indrastoeti Siti Poerwanti; Yulina Dwi Ayu Putri Rahmawati (Universitas Sebelas Maret, 2023)
The aim of this research is to improve the understanding of the concept of the change of object form on the fourth grade students of State Elementary School Tlogorandu 01 Klaten in academic year 2016/2017 by applying the learning model of Treffinger.This research is in the form of Classroom Action Reseach (CAR) which was conducted in two cycles. Each cycle consists of four steps: (1) planning; (2) action phase; (3) observation; and (4) reflection. The subjects of study were teacher and students of fourth grade students of State Elementary School Tlogorandu 01 Klaten in the academic year 2016/ 2017 consisting of 30 students. The data were collected through interviews, observations, documentation, and tests. The data validity was triangulation of resources and triangulation of technique. The data analyzed technique used interactive analysis model which consists of three basic phases are: data reduction, data display, and taking the conclusion or verification. The result of the research shows that the average value of the class on pre cycle is was 56,00; then in the first cycle the average grade increased to 66,25; and in the second cycle the average grade increased to 79,17. Before the action of research, students who acquired more than or equal to 70 were 7 students (23,33%), first cycle the number of the students increased to 15 (50%), and the second cycle the number of the students increased again became 26 students (86,67%). Based on the result finding above, it can be concluded that the application of the learning model of Treffinger can improve the understanding of the concept of the change of object form for students in fourth grade students of State Elementary School Tlogorandu 01 Klaten in the academic year2016/ 2017.